Regulation of data-driven market power in the digital economy: Business value creation and competitive advantages from big data. (June 2023) - Fast, Victoria; Schnurr, Daniel; Wohlfarth, Michael
Recent high-profile antitrust cases and policy proposals have put a spotlight on the relationship between firms' access to big data and sustained competitive advantages in digital markets. In Europe, concerns about data-driven market power have led policymakers to propose far-reaching regulations of information technology (IT) in these markets. Despite the global policy relevance, the regulation of big data and its competitive effects has so far received little attention in information systems (IS) research. This article addresses this research gap by developing an overarching framework for future IS research on the role of IT for the regulation of data-driven market power. The proposed research framework builds upon a three-part analysis: First, we review the academic literature and show that there is extensive, although nuanced, empirical evidence for business value creation from big (user) data. Second, we draw on the resource-based view of the firm and recent policy reports to derive six facilitating factors that enable firms to establish market power based on sustained data-driven competitive advantages. Third, we characterize three regulatory approaches to govern market power and competition in data-driven digital markets: (i) empowering consumers, (ii) data openness, and (iii) limiting data scale. For each of these approaches, we highlight the key role of IT artifacts in mediating the effect of regulatory rules on actual practice.